EVOLUSI DALAM WACANA ORGANISASI DAN LINGKUNGAN: SUATU TINJAUAN KRITIS - Octavina, Melya (Performance, 2011)
Most of organization and environment (O&E) researchs have be aimed to environment, and there are many deferences approach in organization and environment researchs. Organizations theory not enought to discuss environment contex because of limitation in organizational environment idea. Organization and environment material still interesting to discuss in research strategy.